2017
DOI: 10.1177/0895904817719517
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Cognitive Interpretation of U.S. Global Education Initiatives

Abstract: Scholars and policymakers in the United States argue that developing global competence is essential to preparing K-12 students for the increasingly interconnected and interdependent world. Given this increased focus, considering implications for teachers is critical. This qualitative-interpretive study applies a sensemaking framework, drawing on interview data from teachers in the Washington, D.C. metro area to understand their cognitive interpretation of increasing calls to internationalize U.S. schooling. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Therefore, as pedagogical leaders, principals are expected to provide their teachers with emotional support, which is essential for helping them make decisions regarding the acceptance or rejection of reform messages (Saarivirta & Kumpulainen, 2016). In this regard, Maitlis and Christianson (2014) have shown that positive motivational dynamics enable discussions which engage members in deeper sense-making and greater agreement about an appropriate course of action, whereas motivational dynamics that are mixed or negative are associated with more superficial sense-making of policy demands and a failure to act collectively (Siczek & Engel, 2017). Furthermore, emotions have played an important part in framing national external demands into school practices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as pedagogical leaders, principals are expected to provide their teachers with emotional support, which is essential for helping them make decisions regarding the acceptance or rejection of reform messages (Saarivirta & Kumpulainen, 2016). In this regard, Maitlis and Christianson (2014) have shown that positive motivational dynamics enable discussions which engage members in deeper sense-making and greater agreement about an appropriate course of action, whereas motivational dynamics that are mixed or negative are associated with more superficial sense-making of policy demands and a failure to act collectively (Siczek & Engel, 2017). Furthermore, emotions have played an important part in framing national external demands into school practices.…”
Section: Discussionmentioning
confidence: 99%
“…Required to implement education reforms, educators find themselves under a hail of external demands that urge them to either truly carry out a process of change, or rather find ways of getting around the reform and maintain their current practices (Murphy and Torre, 2013). As, in addition, implementing an education reform is a continuous endeavour (Li, 2017; McDonnell and Weatherford, 2016; Siczek and Engel, 2017; Young and Lewis, 2015), it necessarily creates a gap between aspirations and capacities, and, as school environment changes rapidly, this constantly requires responses beyond educators’ ordinary repertory (Saltrick, 2010).…”
Section: Individual Sense-making View Of Reform Implementationmentioning
confidence: 99%
“…Furthermore, Williams (2018) argues that teacher educators valued their opportunities to learn through study abroad experiences, which provided a stronger foundation for their own teaching, and challenged their own thinking of how to teach in contexts that were very different from their own. Siczek and Engel (2019) cite the work of Merry Merryfield (2000), pointing out that teacher educators who have experienced life outside of the mainstream societal categories of race, ethnicity, social class, language, or national belonging are more often than not more successful at building global perspectives into education. Furthermore, Duckworth and Maxwell (2014) argue that any form of social justice focused curriculum requires more effective preparation of mentors if they are truly going to focus on larger transformative actions of change.…”
Section: Perspectives On Internationalization Of Educationmentioning
confidence: 99%